IMPORTANCE OF METAPHOR IN DEVELOPING COHESION (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article offers a thorough examination of the ways in which metaphors are employed in modern English to assess ideas. The evaluation criteria that determine whether metaphors are evaluable are defined, and modifications are both an object of evaluation. The means and conditions for changing the evaluability of metaphors are systematized, axiological types of lexical and semantic groups of metaphors are distinguished, and the agent as a donor of evaluation in the semantic structure of metaphors is taken into account. In addition to offering a typology of demographic, sociocultural, and national cultural variables of metaphor evaluability, this study demonstrates the pragmatic use of evaluative metaphors. The axiological status of the metaphor is established by providing a comprehensive analysis of the semantic, syntactic, pragmatic, and sociolinguistic elements of the metaphor's evaluation in modern English.